Wilson Simonal in field: reflections on the album México 70 (Per Musi, 2013)
Analysis of Wilson Simonal’s Mexico 70 album released in 1970 by the Mexican record label Odeon. We aim at understanding how the internal dimensions of the album, especially regarding the musical-aesthetic guidelines, condensed some symbolic conflicts present in the internationalization culture process and the phonographic industry consolidation in Brazil. After articulating the relations between soccer, media, popular music and the Brazilian State with a musical appreciation of each track on the album, we confronted our partial conclusions with some recurring concepts in the literature that deals with Brazilian culture and Brazilian popular music in the 1970s, in order to suggest a possible analytical approach to think the relation between Brazilian popular music and the political and cultural context of this period.